Langmuir–Blodgett Film Properties of Based on Calix[4]Resorcinarene and the Detection of Those Against Volatile Organic Compounds - Şen, Sibel; Çapan, Rıfat; Özbek, Zikriye; Özel, Mehmet Emin; Stanciu, George A.; Davis, Frank (Springer Heidelberg, 2019)
To determine their inherent properties, thin films of calix[4]resorcinarene (C11AMINE) were deposited using the Langmuir– Blodgett (LB) technique onto a suitable substrate. Prior to the LB thin film preparation, this molecule was first studied at the air–water interface. For the characterization of the deposited film, UV–visible absorption spectroscopy and atomic force microscopy were used. Characterization results indicated that the Langmuir monolayer can be transferred from the water surface onto a glass or a quartz substrate with a transfer ratio of over 95%. This shows that this material is suitable for the preparation of high quality, uniform LB films. Later, gas sensing properties and thickness of these thin films were investigated using the surface plasmon resonance method. Thicknesses and the refractive index values of the C11AMINE films were obtained for differing number of layers. Then, the gas sensing properties towards vapours of four volatile organic compounds were examined: chloroform, benzene, toluene and ethanol. Reversible changes in the optical behaviour of thin films of C11AMINE were observed. It is found that thin films of this material are highly selective towards chloroform vapour, with rapid response and recovery times, making them suitable for practical chloroform-detection applications.